Rearranged oleanane type saponins, astraisoolesaponins A1–A3 and B, from the stems of Astragalus membranaceus (Fisch.) Bge. var. mongholicus (Bge.) Hsiao. Issue 44 (3rd November 2016) - Zhang, Yi; Guo, Yuan-Qiang; Li, Xiao-Xia; Ruan, Jing-Ya; Wang, Ting-Ting; Li, Jian; Han, Li-Feng; Yu, Hai-Yang; Wang, Tao
Abstract: Four novel saponins, astraisoolesaponins A1 –A3 and B (1 –4 ) were isolated from the stems of Astragalus membranaceus (Fisch.) Bge. var. mongholicus (Bge.) Hsiao. Spectroscopic analysis indicated that1 –4 are the first example of saponins possessing a 28-methyl-rearranged carbon skeleton. Their absolute configurations were determined by electronic circular dichroism (ECD) calculations. Both3 and4 displayed triglyceride accumulation inhibitory effects in HepG2 cells and glucose uptake increase effects on L6 cells. Graphical abstract: